Spatial patterns of sediment connectivity in terraced lands: Anthropogenic controls of catchment sensitivity. (29th November 2017) - Calsamiglia, Aleix; Fortesa, Josep; García‐Comendador, Julián; Lucas‐Borja, Manuel E.; Calvo‐Cases, Adolfo; Estrany, Joan
Abstract: In recent decades, the dynamics of global change in developed countries has led to significant alterations in the hydrological and sediment dynamics of terraced land. Agricultural terraces were built to control overland flow and prevent erosion, acting as buffers and barriers throughout the sediment cascading system. Their abandonment and degradation increase the sensitivity of the catchment, promoting the collapse of dry‐stone walls and the reworking of stored sediment. In this study, a geomorphometric index of connectivity—derived from high‐resolution LiDAR data (0.9 pt/m, RMSE < 0.2 m)—analysed the spatial patterns of structural connectivity in a small Mediterranean catchment (4.8 km 2 ) characterized by a massive presence of terraces (37% of the surface area). The morphological characteristics of these anthropogenic features generated a dual effect: (a) general disconnectivity between different compartments of the catchment and (b) concentration of water and sediment flows along preferential pathways promoted by a cascade effect of collapse within the terraced areas. The fieldwork found that 73% of wall collapses were located on these pathways that showed high index of connectivity values (>Q8). This spatial matching was related to feedback dynamics between structural and functional connectivity, in which the failure of walls increases the concentration of runoff, which in turn accelerates the hydraulic processes causing their collapse. Identifying the most connected pathways within the most vulnerable structures in an integrated analysis could be a cost‐effective strategy for establishing priority areas for the management of terraced lands.